2014
DOI: 10.1094/mpmi-12-13-0365-r
|View full text |Cite
|
Sign up to set email alerts
|

An ATP-Binding Cassette Pleiotropic Drug Transporter Protein Is Required for Xenobiotic Tolerance and Antagonism in the Fungal Biocontrol Agent Clonostachys rosea

Abstract: ATP-binding cassette (ABC) transporters mediate active efflux of natural and synthetic toxicants and are considered to be important for drug tolerance in microorganisms. In biological control agents (BCA), ABC transporters can play important roles in antagonism by providing protection against toxins derived from the fungal prey and by mediating the secretion of endogenous toxins. In the present study, we generated deletion and complementation strains of the ABC transporter abcG5 in the fungal BCA Clonostachys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 48 publications
5
105
0
5
Order By: Relevance
“…Putative transformants were selected on a plate containing hygromycin (200 μg/ml). Validation of homologous integration of the deletion cassettes in putative transformants was performed using a PCR screening approach with primer combinations targeting the hph gene (Hyg F/Hyg R) and sequences flanking the deletion cassettes (Appendices and ) as described previously (Dubey, Jensen, & Karlsson, ; Dubey et al., ). RT‐PCR analysis was conducted on WT and gene deletion strains using RevertAid premium reverse transcriptase (Fermentas, St. Leon‐Rot, Germany) and primer pairs specific for the respective genes (Appendix ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative transformants were selected on a plate containing hygromycin (200 μg/ml). Validation of homologous integration of the deletion cassettes in putative transformants was performed using a PCR screening approach with primer combinations targeting the hph gene (Hyg F/Hyg R) and sequences flanking the deletion cassettes (Appendices and ) as described previously (Dubey, Jensen, & Karlsson, ; Dubey et al., ). RT‐PCR analysis was conducted on WT and gene deletion strains using RevertAid premium reverse transcriptase (Fermentas, St. Leon‐Rot, Germany) and primer pairs specific for the respective genes (Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…Several biocontrol mechanisms are reported in C. rosea , including direct parasitism of pathogenic fungi (Li, Huang, Kokko, & Acharya, ; Yu & Sutton, ), antibiosis (Pachenari & Dix, ; Rodriguez et al., ), production of fungal cell wall degrading enzymes (Chatterton & Punja, ; Mamarabadi, Jensen, & Lubeck, ), induction of plant defence reactions (Lahlali & Peng, ; Roberti et al., ) and plant growth promotion (Roberti et al., ). Tolerance towards, and detoxification of, toxic metabolites produced by the fungal prey is also reported to be an important biocontrol trait in C. rosea (Dubey, Jensen, & Karlsson, ; Kosawang, Karlsson, Velez et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…S2e). Previous studies have showed that expression of hygB in C. rosea does not result in any detectable growth-or biocontrol-related phenotypes (Dubey et al, 2014b;Lübeck et al, 2002).…”
Section: Generation and Validation Of C Rosea Chic2 Deletion Strainsmentioning
confidence: 99%
“…As ABC transporters are known to display some promiscuity in their substrates, it is likely that many transporters protect from SMs produced by other fungi 35 . This can be illustrated in Neurospora crassa , a fungus sensitive to cer-cosporin that possesses a transporter conferring some resistance to the toxin 36 , or in the biocontrol fungus Clonostachys rosea , which contains an ABC transporter protective against the Fusarium mycotoxin zearalenone as well as several fungicides 37 .…”
Section: Self-protection Encoded In the Bgcmentioning
confidence: 99%